2021
DOI: 10.3390/ijerph182312372
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Sexuality Workshop for Nurse Aides in Long-Term Care Facilities

Abstract: Background: In long-term care facilities, there are frequent conflicts related to elderly residents’ sexual expression. Nurse aides usually handle such conflicts with negative or negligent attitudes; therefore, elderly sexuality is considered “problem behavior” and is stigmatized. Objectives: This study aimed to improve elderly residents’ quality of sexual life by enhancing nurse aides’ knowledge and attitudes toward elderly sexuality through sexuality workshops. Methods: A quasi-experimental study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Our results are consistent with a prior study that showed that anti-sexual harassment programs can be effective for improving knowledge and attitudes among nurse aides in long term care facilities [24]. That study noted that fear of speaking up and not knowing how to respond were associated with less personal safety [19], [24], [25]. Another study found a significant positive correlation between personal safety and the fear of sexual harassment and demonstrated that a culturally sensitive and institutionally-based approach was not only useful at the individual level, it positively affected workplace culture for women at the institutional level [26].…”
Section: Effectiveness Of the Sexual Harassment Prevention Programsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results are consistent with a prior study that showed that anti-sexual harassment programs can be effective for improving knowledge and attitudes among nurse aides in long term care facilities [24]. That study noted that fear of speaking up and not knowing how to respond were associated with less personal safety [19], [24], [25]. Another study found a significant positive correlation between personal safety and the fear of sexual harassment and demonstrated that a culturally sensitive and institutionally-based approach was not only useful at the individual level, it positively affected workplace culture for women at the institutional level [26].…”
Section: Effectiveness Of the Sexual Harassment Prevention Programsupporting
confidence: 92%
“…The theme "ability to respond in an effective manner" refers to an important aspect of problem solving, contrasting active behavior with a more conservative, deferential attitude. Problem solving is a universally valued job skill, so understanding the critical components of problem solving can help to demonstrate healthy behavior and logical thinking [19]. Attitudes can predict behaviors, such as specific actions to take when encountering and dealing with sexual harassment at work, and can influenced by practical training for FNAs [19].…”
Section: Content Analysis Of Focus Group Discussion On Sexual Harassmentmentioning
confidence: 99%
See 3 more Smart Citations